tìm giá trị m để giá trị biểu thức bằng 1 a. (3m-5)/(m-1) + (2m-5)/(2-m) = 1 b. (9m-7)/(3m-2) + (5-4m)/(2m-3) = 1 c. (2m-9)/(2m-5) +-(3m)/(2-3m) -1

Question

tìm giá trị m để giá trị biểu thức bằng 1
a. (3m-5)/(m-1) + (2m-5)/(2-m) = 1
b. (9m-7)/(3m-2) + (5-4m)/(2m-3) = 1
c. (2m-9)/(2m-5) +-(3m)/(2-3m) -1 = 1
d. (m-3/(m+3) – (1-3m)/(1+3m) -1 = 1

in progress 0
Aaliyah 5 ngày 2021-12-05T07:22:19+00:00 2 Answers 1 views 0

Answers ( )

    0
    2021-12-05T07:23:21+00:00

    a) 

    $\dfrac{3m-5}{m-1} + \dfrac{2m-5}{2-m} = 1$

    $⇔ \dfrac{(3m-5)(2-m) + (2m-5)(m-1)}{(m-1)(2-m)} =1$

    $⇔ (-3m^2 +11m – 10) + (2m^2 -7m + 5) = -m^2 +3m – 2$

    $⇔ m = 3$
    Vậy $m = 3$

    b) 

    $\dfrac{9m-7}{3m-2} + \dfrac{5-4m}{2m-3} = 1$

    $⇔ \dfrac{9m-7}{3m-2} – \dfrac{4m-5}{2m-3} = 1$

    $⇔ \dfrac{(9m-7)(2m-3) – (4m-5)(3m-2)}{(3m-2)(2m-3)} = 1$

    $⇔ 18m^2 -41m + 21 – (12m^2-23m + 10) = 6m^2 -13m + 6$

    $⇔ -5m = -5$

    $⇔ m = 1$

    Vậy $m = 1$

    c)

    $\dfrac{2m-9}{2m-5} – \dfrac{3m}({2-3m} -1 = 1$

    $⇔ \dfrac{(2m-9)(2-3m)-3m(2m-5)}{(2m-5)(2-3m)}=2$

    $⇔ (2m-9)(2-3m)-3m(2m-5)=2(2m-5)(2-3m)$

    $⇔ -6m^2-18+31m-6m^2+15m$

    $=-12m^2-20+38m$

    $⇔  2+8m=0$

    $⇔  8m=-2$

    $⇔ m= \dfrac{-1}{4}$

    Vậy $m= \dfrac{-1}{4}$

    d)

    $\dfrac{m-3}{m+3} – \dfrac{1-3m}{1+3m} -1 = 1$

    $⇔ \dfrac{(m-3)(1+3m)-(1-3m)(m+3)}{(m+3)(1+3m)}=2$

    $⇔ (m-3)(1+3m)+(3m-1)(m+3)=2(m+3)(1+3m)$

    $⇔  3m^2-3-8m+3m^2-3+8m$

    $=6m^2+6+20m$

    $⇔  12+20m=0$

    $⇔  20m=-12$

    $⇔  m=\dfrac{-3}{5}$

    Vậy $m=\dfrac{-3}{5}$

    #NoCopy 

    Cho Mình Câu Trả Lời Hay Nhất Nhé ^.^

    0
    2021-12-05T07:24:11+00:00

    a. 

    ` (3m-5)/(m-1) + (2m-5)/(2-m) = 1`

    `⇔ \frac{(3m-5)(2-m)+(2m-5)(m-1)}{(m-1)(2-m)}=1`

    `⇔ (3m-5)(2-m)+(2m-5)(m-1)=(m-1)(2-m)`

    `⇔ -3m^2-10+11m+2m^2+5-7m=-m^2-2+3m`

    `⇔ -m^2-5+4m=-m^2-2+3m`

    `⇔ m-3=0`

    `⇔  m=3`

    b.

    `(9m-7)/(3m-2) + (5-4m)/(2m-3) = 1`

    `⇔ \frac{(9m-7)(2m-3)+(5-4m)(3m-2)}{(3m-2)(2m-3)}=1`

    `⇔ (9m-7)(2m-3)+(5-4m)(3m-2)=(3m-2)(2m-3)`

    `⇔ 18m^2+21-41m-12m^2-10+23m=6m^2+6-13m`

    `⇔ 11-18m=6-13m`

    `⇔ 13m-18m=6-11`

    `⇔ -5m=-5`

    `⇔ m=1`

    c.

    ` (2m-9)/(2m-5) -(3m)/(2-3m) -1 = 1`

    `⇔ \frac{(2m-9)(2-3m)-3m(2m-5)}{(2m-5)(2-3m)}=2`

    `⇔ (2m-9)(2-3m)-3m(2m-5)=2(2m-5)(2-3m)`

    `⇔ -6m^2-18+31m-6m^2+15m=-12m^2-20+38m`

    `⇔  2+8m=0`

    `⇔  8m=-2`

    `⇔ m= -1/4`

    d.

    ` (m-3)/(m+3) – (1-3m)/(1+3m) -1 = 1`

    `⇔ \frac{(m-3)(1+3m)-(1-3m)(m+3)}{(m+3)(1+3m)}=2`

    `⇔ (m-3)(1+3m)+(3m-1)(m+3)=2(m+3)(1+3m) `

    `⇔  3m^2-3-8m+3m^2-3+8m=6m^2+6+20m`

    `⇔  12+20m=0`

    `⇔  20m=-12`

    `⇔  m=-3/5`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )